Analisis Manajemen Persediaan Bahan Baku Pada Pabrik Tahu Ditinjau Dari Perspektif Bisnis Islam: ( Studi Pada Pabrik Tahu Di Jagabaya Bandar Lampung ) - Budi Herlyanto; Weny Rosilawaty; Fatih Fuadi (JURNAL RISET MANAJEMEN (JURMA), 2024)
Production problems are a very important problem for business actors because they can affect the profits they earn. The smoothness of production itself is influenced by whether or not the raw materials will be used. In this case, raw material inventory management can help reduce possible risks. Raw material inventory management is the most active element in company operations which is continuously obtained. In this case, researchers use the Safety Stock, Economiq Order Quantity (EOQ) and Reorder point inventory management methods to optimize the purchase of raw material inventory so that it becomes optimal and efficient. In this research, problems were found at the Tofu Factory regarding raw material supplies. In this case, the Tofu Factory always experiences a shortage of raw material stock and experiences waste in the costs incurred. This resulted in the Tofu Factory experiencing delays in deliveries to consumers. The results of the analysis show the use of raw material inventory management methods applied at the Jagabaya tofu factory, namely SafetyStock, Economic Order Quantity (EOQ) and Reorder Point. The implementation of this method is not optimal so this method does not work as it should because of several inhibiting factors. The management of raw material supplies at the Jagabaya tofu factory still does not use a structured method, so that in the production process stock runs out often occur. Therefore, raw material inventory management at tofu factories is only based on estimated sales numbers without clear calculations.